AMMONIUM REDOX-RESPONSIVE RECEPTORS CONTAINING MULTIPLE FERROCENE AND QUINONE REDOX-ACTIVE CENTERS ATTACHED TO DI-AZA AND TRI-AZA CROWN-ETHER MACROCYCLES - Beer, P; Crowe, D; Ogden, M; Drew, M; Main, B (1993)
Eight new redox-active di- and tri-aza crown ether macrocyclic ligands containing multiple ferrocene and quinone moieties have been prepared, including the first reported mixed ferrocene-quinone macrocyclic ligand. Solution 1H and 13C NMR complexation studies suggest these ligands form 1:1 stoichiometric complexes with ammonium as guest cation. Single-crystal structures of the hydrogen hexafluorophosphate salt of 7,16-bis(ferrocenylmethyl)-1,4,10,13-tetraoxa-7,16-diazacyclooctadecane and the ammonium complex of 4,10,16-tris(ferrocenylmethyl)-1,7,13-trioxa-4,10,16-triazacyclooctadecane have also been determined. Electrochemical investigations reveal the respective ferrocene-ferrocenium redox couples of most of the ligands are perturbed to more positive potentials on co-ordination of NH4+ and K+ guest cations. The above tris(ferrocenylmethyl) ligand selectively binds and electrochemically recognises NH4+ in the presence of equimolar concentrations of K+. Secondary amide-linked ferrocene aza crown ether ligands electrochemically sense the NH4+ guest cation primarily via host ferrocenecarboxide carbonyl oxygen-H-NH3+ hydrogen-bonding electrostatic interactions.